Family factors and adolescents' substance abuse: a study of adolescent substance abusers in Ilorin, Kwara State (2015)
There has been a plethora of studies on the relationship between family factors and adolescents' substance abuse. However, few studies have been done on the impact of religious training in home and parental substance abuse on adolescents' substance abuse in Nigeria. Therefore, the objective of this study was to fill this fundamental gap. The study was an explorative type while a survey method was applied. The sample of the study comprised four hundred and twenty-six respondents (n=426) from twelve selected secondary schools in florin, Kwara State. The respondents were selected, using snowballing sampling technique. Questionnaire technique was used to collect quantitative data; while In-depth interview was adopted to collect qualitative information. Two hypotheses were formulated for the study, and they were tested using Chi-Square at 0.05 level of significance. Content analysis was employed to analyze qualitative information obtained from In-depth interview. The results of analysis showed religious training in homes as a protective factor; while parental substance abuse as a risk factor of adolescents' substance abuse. Based on these findings, it was recommended that parents should inculcate religious values and ethics into their wards.